European Academy of Andrology (EAA) guidelines on investigation, treatment and monitoring of functional hypogonadism in males: Endorsing organization: European Society of Endocrinology. (20th March 2020) - Corona, Giovanni; Goulis, Dimitrios G.; Huhtaniemi, Ilpo; Zitzmann, Michael; Toppari, Jorma; Forti, Gianni; Vanderschueren, Dirk; Wu, Frederick C.
Abstract: Background: Evidence regarding functional hypogonadism, previously referred to as 'late‐onset' hypogonadism, has increased substantially during the last 10 year. Objective: To update the European Academy of Andrology (EAA) guidelines on functional hypogonadism. Methods: Expert group of academicians appointed by the EAA generated a series of consensus recommendations according to the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) system. Results: The diagnosis of functional hypogonadism should be based on both the presence of clinical symptoms supported by repeatedly low morning fasting serum total testosterone (T) measured with a well‐validated assay, after exclusion of organic causes of hypogonadism. Lifestyle changes and weight reduction should be the first approach in all overweight and obese men. Whenever possible, withdrawal/modification of drugs potentially interfering with T production should be advised. Testosterone replacement therapy (TRT) is contraindicated in men with untreated prostate or breast cancer, as well as severe heart failure. Severe low urinary tract symptoms and haematocrit >48%‐50% represent relative contraindications for TRT. Prostate‐specific antigen and digital rectal examination of the prostate should be undertaken in men >40 years of age before initiating TRT to exclude occult prostate cancer. Transdermal T should be preferred for initiation of TRT, whereas gonadotrophin therapy is only recommended when fertility is desired in men with secondary hypogonadism. TRT is able to improve sexual function in hypogonadal men. Other potential positive outcomes of TRT remain uncertain and controversial. Conclusion: TRT can reliably improve global sexual function in men with hypogonadism in the short term. Long‐term clinical benefits, and safety of TRT in functional hypogonadism, remain to be fully documented. Clinicians should therefore explicitly discuss the uncertainties and benefits of TRT and engage them in shared management decision‐making.